Copper foil and composite film

JP7630546B2Active Publication Date: 2025-02-17FURUKAWA ELECTRIC CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023057266
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-02-17
Estimated Expiration
2043-03-31

AI Technical Summary

Benefits of technology

【0009】 本発明に係る銅箔は、樹脂との優れた密着性と優れた成形性を有し、その銅箔を使用した複合フィルムは、優れた成形性を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630546000002
    Figure 0007630546000002
  • Figure 0007630546000003
    Figure 0007630546000003
  • Figure 0007630546000001
    Figure 0007630546000001
Patent Text Reader

Abstract

To provide a copper foil with excellent resin adhesion and formability.SOLUTION: At least one surface 10a of two surfaces of a copper foil 10 is an uneven surface with irregularities. An arithmetic average waveform Wλa of the uneven surface is 10 μm or more and 80 μm or less, and an arithmetic average inclination WΔa is 0.4° or more and 4° or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to copper foils and composite films. [Background technology]

[0002] In recent years, electronic devices such as smartphones, medical devices, and automobiles have become highly integrated and perform better, and at the same time, the importance of EMI (Electromagnetic Interference) countermeasures to suppress EMI in electronic devices is increasing. Therefore, in order to prevent problems such as malfunction of the electronic devices and deterioration of communication data quality due to electromagnetic waves from inside and outside the electronic device's housing, components such as noise filters and electromagnetic wave absorbing sheets are used in electronic devices. Among such materials, a composite film called an EMI countermeasure film is used in many electronic devices. The EMI countermeasure film is a composite film having a structure in which an electromagnetic wave shielding layer made of a metal or the like and a resin layer made of a conductive resin material are laminated. As the electromagnetic wave shielding layer, copper foil is sometimes used from the viewpoints of high conductivity, shielding properties, and industrial productivity.

[0003] When attaching an EMI countermeasure film to an electronic device, the electromagnetic wave shielding layer is usually attached to the metal part inside the electronic device via a resin layer. In recent years, as the mounting density of parts in electronic devices such as smartphones increases, EMI countermeasure films are often mounted in narrow spaces. In addition, as electronic devices are becoming increasingly higher frequency, EMI countermeasure films are required to sufficiently suppress the leakage of electromagnetic noise. Therefore, EMI countermeasure films are required to have excellent formability so that they can easily deform to follow the shape of the object to which they are attached, such as integrated circuits and flexible substrates, when attached to the object to which they are attached.

[0004] When attaching an EMI countermeasure film to an object, the EMI countermeasure film may be subjected to three-dimensional processing such as bulging and drawing. However, since the copper foil is thin, there is a risk of the copper foil being thinned and cracked. If the copper foil surface has irregularities, the concave portions are particularly thin and prone to stress concentration, so that the copper foil is easily thinned and cracked when the three-dimensional processing is performed. Therefore, the EMI countermeasure film is required to have excellent formability, that is, to be less likely to crack even when three-dimensional processing is performed, and to easily deform to follow the shape of the object to which the film is attached. In addition, the EMI countermeasure film is also required to have excellent adhesion between the copper foil and the resin layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6805382 [Patent Document 2] Patent No. 6379071 Summary of the Invention [Problem to be solved by the invention]

[0006] Patent Documents 1 and 2 disclose composite films having excellent formability. However, in electronic devices such as smartphones, the mounting density of components is becoming increasingly high, and therefore, composite films such as EMI countermeasure films are required to have further improved formability. An object of the present invention is to provide a copper foil having excellent adhesion to resin and excellent formability, and a composite film using the copper foil having excellent formability. [Means for solving the problem]

[0007] In order to solve the above problems, the present inventors have conducted extensive research focusing on the surface shape of copper foil. As a result, they have found that if a gently uneven shape is uniformly provided on the surface of the copper foil, when the copper foil is subjected to three-dimensional processing, the reduction in thickness occurs in a distributed manner in each of the depressions uniformly present on the surface of the copper foil, and therefore it is possible to suppress the phenomenon in which only certain depressions are reduced in thickness and cause cracks in the copper foil.

[0008] That is, in one embodiment of the copper foil of the present invention, at least one of the two surfaces of the copper foil is an uneven surface having projections and recesses, an arithmetic mean wavelength Wλa of the uneven surface being 10 μm or more and 80 μm or less, and an arithmetic mean tilt angle WΔa of 0.4° or more and 4° or less. A composite film according to another embodiment of the present invention comprises the copper foil according to the above-mentioned embodiment of the present invention and a resin layer laminated on one or both of the two surfaces of the copper foil. Effect of the Invention

[0009] The copper foil according to the present invention has excellent adhesion to resin and excellent formability, and a composite film using the copper foil has excellent formability. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view illustrating a composite film according to one embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view illustrating a modified example of the composite film of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] An embodiment of the present invention will be described. Note that the embodiment described below is merely an example of the present invention. In addition, various modifications and improvements can be made to this embodiment, and such modifications and improvements can also be included in the present invention. As shown in FIG. 1, the composite film 1 of this embodiment comprises a copper foil 10 forming an electromagnetic wave shielding layer, and a resin layer 20 made of a conductive resin material and laminated on one surface 10a of the two surfaces of the copper foil 10.

[0012] Of the two surfaces of the copper foil 10, the surface 10a on which the resin layer 20 is laminated is an uneven surface having an arithmetic mean wavelength Wλa of 10 μm or more and 80 μm or less, and an arithmetic mean tilt angle WΔa of 0.4° or more and 4° or less. Of the two surfaces of the copper foil 10, the surface on which the resin layer 20 is not laminated is a surface that does not satisfy the conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa.

[0013] That is, one surface 10a of the two surfaces of the copper foil 10 is an uneven surface that satisfies the conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa, and the other surface is a surface that does not satisfy the conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa, and a resin layer 20 is laminated on the uneven surface, thereby producing a composite film 1.

[0014] Due to this configuration, the copper foil 10 and the composite film 1 have excellent formability. In other words, when the composite film 1 is subjected to three-dimensional processing, the copper foil 10 is less likely to crack. In addition, when the composite film 1 is attached to an object to be attached, such as an integrated circuit or a flexible board, the composite film 1 easily deforms to follow the shape of the object to be attached.

[0015] In addition, if the uneven surface satisfies the above conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa, the thickness of the copper foil 10 is highly uniform and the adhesion to the resin layer 20 is excellent. Furthermore, if the uneven surface satisfies the above conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa, the uneven surface has unevenness, but the unevenness is gentle, resulting in a smooth and highly glossy surface.

[0016] Because of such excellent performance, the composite film 1 according to this embodiment can be suitably used as an EMI countermeasure film. Therefore, the composite film 1 according to this embodiment can be used as an EMI countermeasure film for various electronic devices and exhibits excellent EMI resistance. The composite film 1 according to this embodiment can be suitably used for electronic devices such as smartphones, medical devices, and automobiles, and can be suitably used in particular for mobile electronic devices such as smartphones.

[0017] The composite film 1 in FIG. 1 is an example in which only one surface 10a of the two surfaces of the copper foil 10 is an uneven surface that satisfies the conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa, and a resin layer 20 is laminated on the surface 10a, but the composite film of the present invention is not limited to this example.

[0018] For example, only one surface 10a of the two surfaces of the copper foil 10 may be an uneven surface that satisfies the above conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa, or both of the two surfaces of the copper foil 10 may be uneven surfaces that satisfy the above conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa.

[0019] When only one of the two surfaces, surface 10a, of the copper foil 10 is an uneven surface that satisfies the conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa, the resin layer 20 may be laminated on surface 10a, which is an uneven surface that satisfies the conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa, or the resin layer 20 may be laminated on a surface (the surface opposite surface 10a) that does not satisfy the conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa. In addition, the composite film 1 in Figure 1 is an example in which the resin layer 20 is laminated only on one surface 10a of the two surfaces of the copper foil 10, but the resin layer 20 may be laminated on both of the two surfaces of the copper foil 10.

[0020] The composite film 1 according to the present embodiment may further include at least one of a release film 30, an insulating layer 40, and a carrier film 50. That is, a modified example of the composite film 1 according to the present embodiment may have a structure in which a release film 30 is further laminated on the resin layer 20 as shown in FIG. 2. In addition, a modified example of the composite film 1 according to the present embodiment may have a structure in which an insulating layer 40 for electrically protecting the copper foil 10 is further laminated on the surface 10b opposite to the surface 10a on which the resin layer 20 is laminated, out of the two surfaces of the copper foil 10, as shown in FIG. 2. Furthermore, a modified example of the composite film 1 according to the present embodiment may have a structure in which a carrier film 50, which is a support, is further laminated on the insulating layer 40 as shown in FIG. 2.

[0021] 2 shows an example of a composite film 1 including all of the release film 30, the insulating layer 40, and the carrier film 50, but the modified example of the composite film 1 according to the present embodiment is not limited to this. However, when the resin layer 20 is laminated on both of the two surfaces 10a, 10b of the copper foil 10, the composite film 1 does not include the insulating layer 40 and the carrier film 50.

[0022] The composite film 1 according to this embodiment will be described in further detail below. (1) Copper foil As the copper foil 10 of the composite film 1 according to this embodiment, either an electrolytic copper foil or a rolled copper foil can be used, and a copper foil formed by a known method such as vapor deposition, sputtering, etc. Also, a copper foil whose surface shape and thickness have been adjusted by a known method such as etching, electrolytic polishing, etc. may be used as the copper foil 10 of the composite film 1 according to this embodiment.

[0023] The thickness of the copper foil 10 of the composite film 1 according to this embodiment is preferably 5 μm or more and 30 μm or less. If the thickness of the copper foil 10 is 30 μm or less, springback is unlikely to occur during three-dimensional processing. In addition, if the thickness of the copper foil 10 is 30 μm or less, the composite film 1 is likely to be thin and lightweight, which is suitable for mounting on mobile electronic devices such as smartphones. If the thickness of the copper foil 10 is 5 μm or more, pinholes are unlikely to occur during the manufacturing of the copper foil 10, so that cracks are unlikely to occur in the copper foil 10 during three-dimensional processing. The thickness of the copper foil 10 is more preferably 5 μm or more and 20 μm or less.

[0024] (2) Uneven surfaces The arithmetic mean wavelength Wλa of the uneven surface of the copper foil 10 must be 10 μm or more and 80 μm or less, but is preferably 20 μm or more and 70 μm or less. If the arithmetic mean wavelength Wλa is less than 10 μm, the surface of the copper foil has a high unevenness frequency, which deteriorates the filling of the adhesive and easily impairs adhesion to the resin. If the arithmetic mean wavelength Wλa exceeds 80 μm, the surface of the copper foil has a low unevenness frequency, which makes it difficult to obtain adhesion to the resin and to obtain the effect of preventing cracks during three-dimensional processing.

[0025] The arithmetic mean inclination angle WΔa of the uneven surface of the copper foil 10 must be 0.4° or more and 4° or less, but is preferably 0.6° or more and 3° or less. If the arithmetic mean inclination angle WΔa is less than 0.4°, the unevenness of the copper foil surface is too gentle, making it difficult to prevent cracks during three-dimensional processing. If the arithmetic mean inclination angle WΔa exceeds 4°, the unevenness of the copper foil surface is too steep, making it more likely to cause cracks during three-dimensional processing.

[0026] Furthermore, the arithmetic mean waviness Wa of the uneven surface of the copper foil 10 is preferably 0.07 μm or more and 0.45 μm or less, and more preferably 0.10 μm or more and 0.40 μm or less. If the arithmetic mean waviness Wa is less than 0.07 μm, the surface of the copper foil is too smooth, making it difficult to prevent cracking during three-dimensional processing. If the arithmetic mean waviness Wa exceeds 0.45 μm, the surface of the copper foil is too rough, making the filling of the adhesive poor and easily impairing adhesion to the resin. If the uneven surface of the copper foil 10 satisfies the above conditions for the arithmetic mean waviness Wa, the copper foil 10 and the composite film 1 have excellent formability, and the copper foil 10 has excellent adhesion to the resin layer 20.

[0027] Furthermore, the developed area ratio Sdr of the uneven surface of the copper foil 10 is preferably 0.007 or more and 0.200 or less, more preferably 0.007 or more and 0.100 or less. If the developed area ratio Sdr is less than 0.007, the copper foil surface is too smooth, making it difficult to prevent cracks during three-dimensional processing. If the developed area ratio Sdr exceeds 0.200, the copper foil surface is too rough, making it more likely to crack during three-dimensional processing. If the uneven surface of the copper foil 10 satisfies the above conditions for the developed area ratio Sdr, the copper foil 10 and the composite film 1 have excellent formability.

[0028] (3) Resin layer The resin layer 20 of the composite film 1 according to this embodiment is made of a resin material having electrical conductivity. Examples of the resin material having electrical conductivity include a conductive pressure-sensitive adhesive containing a conductive filler and a conductive adhesive containing a conductive filler. The conductive pressure-sensitive adhesive and the conductive adhesive contain a conductive filler and a resin that impart electrical conductivity to the resin layer 20.

[0029] The conductive adhesive may have adhesiveness at room temperature. The resin contained in the conductive adhesive may be a thermosetting resin or a thermoplastic resin. The conductive adhesive containing a thermosetting resin may be in any of an uncured, B-stage, or cured state in the composite film 1.

[0030] Examples of resins contained in conductive pressure sensitive adhesives and conductive adhesives include epoxy, phenol, amino, alkyd, urethane, synthetic rubber, acrylate, acrylic, silicone, imide, isocyanate, vinyl chloride, vinyl acetate, styrene, and hydrocarbon resins and pressure sensitive adhesives. Among these resins, epoxy resins are preferred because of their excellent heat resistance.

[0031] Examples of the conductive filler include metal particles and carbon particles. Examples of the metal include silver (Ag), platinum (Pt), gold (Au), copper (Cu), nickel (Ni), palladium (Pd), aluminum (Al), solder, and alloys thereof. Examples of the carbon particles include graphite particles, baked carbon particles, and plated baked carbon particles. Among these particles, copper particles and graphite particles are preferred from the viewpoints of moldability and industrial productivity when producing the resin layer 20.

[0032] The thickness of the resin layer 20 is preferably 5 μm or more and 50 μm or less. If the thickness of the resin layer 20 is 5 μm or more, the resin layer 20 can easily conform to the shape and steps of the ground (GND) opening of the printed wiring board or the metal housing of the electronic device, so that the target location can be sufficiently filled with the resin layer 20. On the other hand, if the thickness of the resin layer 20 is 50 μm or less, the flexibility of the composite film 1 is excellent, so that the composite film 1 can be mounted in a thinner space.

[0033] (4) Manufacturing method of copper foil The copper foil having an uneven surface that satisfies the above conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa can be manufactured by a known copper foil manufacturing method. Examples of the copper foil manufacturing method include sandblasting, embossing, etching, plating, etc. Among these methods, plating is suitable for realizing a surface shape with shallow and gentle unevenness. The plating method will be described in detail.

[0034] The copper foil 10 according to this embodiment can be obtained by plating a typical copper foil having smooth surfaces on both sides to convert the surface of the copper foil into an uneven surface that satisfies the above-mentioned conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa. Among various plating methods, a low current density electrolysis method using a mesh anode as the anode is preferred. If a mesh anode is used as the anode, the current distribution on the surface of the copper foil becomes non-uniform, so that a surface shape with shallow and gentle unevenness is easily formed. An example of a mesh anode is a platinum mesh with a mesh of 100 and a wire diameter of 0.07 mm.

[0035] The electrode distance during plating is preferably 20 mm or more and 80 mm or less. If the electrode distance is 20 mm or more, short circuits are unlikely to occur even if the copper foil moves due to the flow of the electrolyte. If the electrode distance is 80 mm or less, the current distribution on the surface of the copper foil is likely to be uneven, and a surface shape with shallow and gentle irregularities is likely to be formed.

[0036] The current density during plating is, for example, 1A / dm 2 More than 10A / dm 2 It is preferable that the current density is 10 A / dm or less. 2 If the current density is less than 1 A / dm, a surface shape with shallow and gentle unevenness is easily formed. 2 If the above conditions are met, a surface shape having shallow and gentle unevenness can be easily formed, and the copper foil 10 according to this embodiment can be produced with high productivity.

[0037] The current density during plating is preferably low as described above. If the current density is high, it will result in so-called roughening plating, which may cause the thickness of the copper foil to become uniform, or the copper foil may break or the roughening particles may fall off during three-dimensional processing, which may prevent the object of the present invention from being achieved. However, the appropriate current density also depends greatly on the composition of the electrolyte (copper concentration, sulfuric acid concentration, etc.), temperature, flow rate, plating time, etc.

[0038] The flow velocity of the electrolyte refers to the average flow velocity of the electrolyte flowing between the electrodes. For example, in a system in which copper foil is transported through the electrolyte, the flow velocity of the electrolyte is the relative speed to the fixed anode, i.e., the transport speed of the copper foil. In a system in which the copper foil is fixed and the electrolyte is made to flow by a pump or the like, the flow velocity of the electrolyte is the volume per unit time of the electrolyte transported between the electrodes by the pump divided by the cross-sectional area of ​​the electrolyte flow path between the electrodes (the cross-sectional area of ​​the electrolyte flow path that appears when the electrolyte flow path is cut by a plane perpendicular to the direction in which the electrolyte flows).

[0039] The following methods can be mentioned as manufacturing methods of the copper foil 10 other than the plating method. For example, a method can be mentioned in which a concave-convex shape is formed in advance by a method such as machining on the surface of a drum, for example made of titanium, used in manufacturing the electrolytic copper foil, and the electrolytic copper foil is manufactured using the drum. According to this method, an electrolytic copper foil having a replica shape of the concave-convex shape formed on the surface of the drum can be obtained.

[0040] Also, for example, a method of performing electrodeposition on a copper foil having a smooth surface to convert the surface of the copper foil into an uneven surface that satisfies the above conditions of the arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa can be mentioned. Methods for controlling the shape of the copper foil surface in electrodeposition include a method of controlling the electrodeposition shape using known organic additives such as glue and thiourea, and a method of controlling the electrodeposition shape using pulse electrolysis or PR electrolysis. These methods may be performed alone or in combination.

[0041] Furthermore, after the copper foil 10 according to this embodiment is manufactured by the above plating method, an anti-rust treatment may be applied to the uneven surface of the copper foil 10. An example of the anti-rust treatment is a plating treatment for coating with a film containing at least one metal selected from nickel, zinc (Zn), chromium (Cr), molybdenum (Mo), cobalt (Co), silicon (Si), and tungsten (W).

[0042] [Example] The present invention will be described in more detail below with reference to examples and comparative examples. Example 1 The matte surface of the rust-free electrolytic copper foil DR-WS manufactured by Furukawa Electric Co., Ltd. was plated to adjust the surface shape of the matte surface, and the arithmetic mean wavelength Wλa, arithmetic mean tilt angle WΔa, arithmetic mean waviness Wa, and developed area ratio Sdr of the matte surface were set as shown in Table 1. The thickness of the copper foil was 10 μm.

[0043] [Table 1]

[0044] <Plating process> The electrolytic solution used in the plating process contained copper and sulfuric acid, with a copper concentration of 40 g / L and a sulfuric acid concentration of 80 g / L. The temperature of the electrolytic solution was 25° C. The anode used was a platinum mesh with a mesh size of 100 and a wire diameter of 0.07 mm.

[0045] The electrode distance during plating was 50 mm, and the current density, plating time, and flow rate of the electrolyte were as shown in Table 1. In Example 1, the copper foil was transported in the stationary electrolyte, so the transport speed of the copper foil was taken as the flow rate of the electrolyte. The plating time was adjusted by adjusting the length of the anode using a shielding plate.

[0046] <Surface shape measurement> The arithmetic mean wavelength Wλa, arithmetic mean tilt angle WΔa, and arithmetic mean waviness Wa of the matte surface (plated surface) were measured as follows: In accordance with the provisions of ISO25178, the matte surface of the copper foil was analyzed using a laser microscope VK-X3000 manufactured by Keyence Corporation, and data analysis was performed using the software attached to the laser microscope. The objective lens magnification of the laser microscope is 50x, the scan mode is laser confocal, the measurement size is 2048 x 1536, the measurement quality is "High Precision", and the pitch is 0.1 μm.

[0047] In the analysis of the matte surface (plated surface) of the copper foil, the line roughness in the direction parallel to the width direction of the copper foil was measured in a multiple line roughness measurement mode. At that time, the line roughness of 9 arbitrary lines within the field of view was measured. Then, the obtained cross-sectional curve was subjected to a filter process of λc: 0.008 mm to obtain a waviness curve, and the arithmetic mean wavelength Wλa, arithmetic mean tilt angle WΔa, and arithmetic mean waviness Wa were obtained from the waviness curve. Such measurements were performed in three arbitrary fields of view, and the average values ​​were taken as the arithmetic mean wavelength Wλa, arithmetic mean tilt angle WΔa, and arithmetic mean waviness Wa of Example 1.

[0048] The arithmetic mean wavelength Wλa and the arithmetic mean tilt angle WΔa are parameters not described in ISO25178, but are parameters described in the Multi-File Analysis Application Reference Manual for the VK-X3000 Series Laser Microscope manufactured by Keyence Corporation, and can be calculated using the software provided with the above-mentioned laser microscope.

[0049] The developed area ratio Sdr of the matte surface (plated surface) was measured as follows: In accordance with the provisions of ISO25178, the matte surface of the copper foil was analyzed using a laser microscope VK-X3000 manufactured by Keyence Corporation, and data analysis was performed using the software attached to the laser microscope. The objective lens magnification of the laser microscope is 100x, the scan mode is laser confocal, the measurement size is 2048 x 1536, the measurement quality is "High Precision", and the pitch is 0.06 μm.

[0050] The developed area ratio Sdr was calculated by performing the following reference surface correction, smoothing image processing, and filtering on the measurement data using the attached analysis software, and then performing calculations on an arbitrary field of view of 100 μm × 100 μm. Such measurements were performed on three arbitrary fields of view, and the average value was taken as the developed area ratio Sdr of Example 1. Reference plane correction: Full surface Smoothing: 3x3, Gaussian Filter processing: L filter 0.025mm

[0051] <Evaluation of moldability> The copper foil of Example 1 was subjected to an Erichsen test. The copper foil was cut to prepare a square test piece with a side of 100 mm. The prepared test piece was then subjected to an Erichsen test according to the standard test prescribed in JIS B7729 (2005). The test was performed so that the plated surface was the side that was pressed and became convex. When the pressing depth reached 1 mm and 2 mm, the test (pressing) was temporarily stopped, and the surface of the test piece was visually observed to confirm whether or not cracks had occurred in the copper foil. The results are shown in Table 1.

[0052] The results of the Erichsen test shown in Table 1 are evaluated based on the following evaluation criteria. A (Pass): No cracks were observed when the indentation depth reached 2 mm. B (Pass): Cracks occurred when the indentation depth reached 2 mm. C (Fail): Cracks occurred when the indentation depth reached 1 mm.

[0053] <Adhesion test> The copper foil of Example 1 was subjected to an adhesion test to evaluate the adhesion to the resin. After the adhesive was applied in a film form to the matte surface (plated surface) of the copper foil, the adhesive was heated at 80°C for 3 minutes to volatilize the solvent in the adhesive, and an adhesive layer with a thickness of 30 μm was formed. In an environment of 22°C, a polyimide film was attached onto the adhesive layer of the copper foil, and the film was pressed using a pressure roller APR-97 for peeling tests manufactured by Imada Co., Ltd., and then allowed to stand for 30 minutes. As a result, the copper foil and the polyimide film were bonded via the adhesive layer.

[0054] The adhesive used was an acrylic adhesive Finetac CT-5030 manufactured by DIC Corp. The polyimide film used was Upilex (registered trademark)-S product number 25S manufactured by UBE Corp. The copper foil and polyimide film were cut to prepare square test pieces with sides of 20 mm. These test pieces were then placed in a thermohygrostat at a temperature of 85°C and a relative humidity of 85%RH, and the surfaces of the test pieces were visually observed at 48 hours and 96 hours to confirm whether or not peeling had occurred between the copper foil and the polyimide film (i.e., whether or not there was any blistering). The results are shown in Table 1.

[0055] The results of the adhesion test shown in Table 1 were evaluated based on the following evaluation criteria. A (Pass): No peeling occurred after 96 hours B (Pass): Peeling occurred after 96 hours C (Fail): Peeling occurred after 48 hours

[0056] (Examples 2 to 13) The copper foil was evaluated in the same manner as in Example 1, except that the plating conditions were changed as shown in Table 1 and the surface shape of the copper foil was adjusted as shown in Table 1. The results are shown in Table 1.

[0057] Comparative Example 1 Except for the fact that no plating treatment was performed, the copper foil was evaluated in the same manner as in Example 1. The results are shown in Table 1. In the adhesion test, a polyimide film was adhered to the matte surface of the copper foil.

[0058] Comparative Example 2 Except for the fact that no plating treatment was performed, the copper foil was evaluated in the same manner as in Example 1. The results are shown in Table 1. In the adhesion test, a polyimide film was adhered to the shiny side of the copper foil.

[0059] Comparative Example 3 Except for using a commercially available non-roughened rolled copper foil (tough pitch copper) instead of the non-rust-proof electrolytic copper foil DR-WS foil and not applying a plating treatment, the copper foil was evaluated in the same manner as in Example 1. The results are shown in Table 1. The thickness of the non-roughened rolled copper foil was 10 μm.

[0060] Comparative Example 4 Except for using a roughened copper foil FV-WS manufactured by Furukawa Electric Co., Ltd. instead of the non-rust-proof electrolytic copper foil DR-WS and not performing plating treatment, the copper foil was evaluated in the same manner as in Example 1. The results are shown in Table 1. The thickness of the roughened copper foil FV-WS is 10 μm.

[0061] Comparative Example 5 A copper foil having a thickness of 10 μm was produced according to the method described in Example 1 of Japanese Patent No. 6910381. The obtained copper foil was used instead of the non-anticorrosive electrolytic copper foil DR-WS foil, and the copper foil was evaluated in the same manner as in Example 1, except that the plating treatment was not performed. The results are shown in Table 1.

[0062] (Comparative Examples 6 to 9) The copper foil was evaluated in the same manner as in Example 1, except that the plating conditions were changed as shown in Table 1 and the surface shape of the copper foil was adjusted as shown in Table 1. The results are shown in Table 1.

[0063] As can be seen from Table 1, the copper foils of Examples 1 to 13 were less likely to crack and had excellent formability, as well as excellent adhesion. In contrast, the copper foils of Comparative Examples 1 to 7 and 9 were prone to cracking and had insufficient formability because the surface shape of the copper foil (arithmetic mean wavelength Wλa and arithmetic mean tilt angle WΔa) did not satisfy the requirements of the present invention. Comparative Example 8 had good formability but insufficient adhesion. [Explanation of symbols]

[0064] 1. Composite film 10...Copper foil 10a Copper foil surface 20...Resin layer

Claims

1. A copper foil comprising: At least one of the two surfaces of the copper foil is an uneven surface having projections and recesses; The copper foil has an arithmetic mean wavelength Wλa of 10 μm or more and 80 μm or less, and an arithmetic mean tilt angle WΔa of 0.4° or more and 4° or less.

2. The copper foil according to claim 1, wherein the arithmetic mean waviness Wa of the uneven surface is 0.07 μm or more and 0.45 μm or less.

3. 2. The copper foil according to claim 1, wherein the developed area ratio Sdr of the uneven surface is 0.007 or more and 0.200 or less.

4. The copper foil according to claim 1, having a thickness of 5 μm or more and 30 μm or less.

5. A composite film comprising the copper foil according to any one of claims 1 to 4 and a resin layer laminated on one or both of the two surfaces of the copper foil.

6. The composite film according to claim 5, which is used as an EMI countermeasure film.

Citation Information

Patent Citations

  • Multi-item immunoassay

    JP1988079071A

  • Copper foil for resin bonding, and its manufacturing method

    JP2003239082A

  • Treated copper foil for copper-clad laminated board and copper-clad laminated board obtained by adhering the treated copper foil onto insulating resin substrate, and printed circuit board using the copper-clad laminated board

    JP2011219790A

  • Roughened copper foil, copper-clad laminate and print circuit board

    JP2022085378A

  • Electromagnetic wave shielding material

    JP6805382B1